A comparative assessment of empirical and lattice Boltzmann method-based drag models for simulation of gas–solid flow hydrodynamics in a bubbling fluidized bed - Luna, Carlos M. Romero [UNESP]; Carrocci, Luis R. [UNESP]; Arce, Gretta L.A.F. [UNESP]; Ávila, Ivonete [UNESP] (Elsevier, 2017)
In simulations of fluidized beds using computational fluid dynamics (CFD), the description of gas–solid flow hydrodynamics relies on a drag model to account for the momentum transfer between gas and solid phases. Although several studies of drag models have been published, there have been few investigations of the application of lattice Boltzmann method (LBM)-based drag models to bubbling fluidized bed simulations. In the present study, a comprehensive comparison of empirical and LBM-based drag models was carried out to assess the performance of these models during simulations of gas–solid flow hydrodynamics in a bubbling fluidized bed. A CFD model using the MFIX code based on the Eulerian–Eulerian approach and the kinetic theory of granular flow was used to simulate a 2D bubbling fluidized bed with Geldart B particles. The simulation results were validated by comparison with experimental data. Statistical analysis of the results shows that LBM-based drag models can reliably model gas–solid flow hydrodynamics in a bubbling fluidized bed.
Keywords: Bubbling fluidized bed; CFD; Drag model; Gas–solid flow hydrodynamics